Digital didactics: technologies & practices - E. V. Voevoda (Дискурс профессиональной коммуникации, 2020)
On April 25, 2020, MGIMO University held the inter-institutional scientific and practical seminar (with international participation) “Digital Didactics: Technologies and Practices” organized by the Department of Pedagogy and Psychology. Educators and researchers from Russia, Belarus and Moldova met in the wake of the COVID-19 pandemic, which sent students and professors online, to discuss the problems related to teaching and learning from home and share the immediate experience of the first month in quarantine conditions. MGIMO welcomed colleagues from Moscow Pedagogical State University, Financial University under the Government of the Russian Federation, Moscow Polytechnic University, Academy of Labour and Social Relations, Esenin Ryazan State University, Pushkin State Russian Language Institute, Belarusian State University, Komrat State University (Moldova), Federal Research Centre Computer Science and Control of the Russian Academy of Sciences. The participants of the seminar discussed the place and role of online courses in university education, ways of presenting teaching material and teaching methods as well as pedagogical and psychological problems in online education.